SUN-492 Unresolved Hyperparathyroidism Due To Mediastinal Parathyroid Adenoma - Brown, Isaiah (J Endocr Soc, 2019)
Background: Mediastinal parathyroid adenomas are found in approximately 1-2% of patients undergoing workup and surgery for primary hyperparathyroidism, although the actual incidence of mediastinal parathyroid glands is higher in autopsy series. Preoperative planning is crucial for optimal intraoperative success. Clinical case: A 75 years-old woman presented with persistent hyperparathyroidism despite prior neck explorations and parathyroidectomy in the 1990s where she had 2 parathyroid glands removed. This was in the era before routine localization studies were performed. Over the decades since, her calcium level peaked at 12 mg/dL, and parathyroid hormone (PTH) levels ranged in the 300-500s pg/mL, but calcium had been able to be kept to less than 11 mg/dL with medical management. Over the past 5 years, she developed worsening renal insufficiency and osteopenia necessitating discussion of reoperation. Neck ultrasound did not identify a parathyroid adenoma. Sestamibi parathyroid scan localized a parathyroid adenoma to the upper mediastinum. CT scan showed a 2 cm substernal mass in the anterior mediastinum slightly below the brachiocephalic vein. Laryngoscopy showed a non-functional right vocal cord consistent with prior right recurrent laryngeal nerve injury. After extensive preoperative counseling of the risks and benefits, including the possible need for hemi-sternotomy, the patient wanted to proceed with reoperation. She underwent attempted transcervical approach to reach the parathyroid adenoma, but the adenoma was beyond reach, and thus a hemi-sternotomy was performed allowing for parathyroidectomy with removal of a 2.5 cm x 1.7 cm adenoma. Given the possibility that the only remaining parathyroid tissue was her ectopic parathyroid adenoma, a portion of the parathyroid adenoma was also autotransplanted onto her abdominal wall subcutaneous tissue. PTH levels decreased from 571 pg/mL to 66 pg/mL. Pathology confirmed hypercellular parathyroid tissue. She initially became hypocalcemic postoperatively but normalized with oral calcium and recovered well. Conclusion: Preoperative imaging is critical in the reoperation for persistent hyperparathyroidism since an ectopic parathyroid is a possible cause. Preoperative planning is essential for a safe and effective reoperation, especially for a mediastinal parathyroid adenoma. Autotransplantation of parathyroid tissue after reoperative parathyroidectomy should be considered to prevent severe hypoparathyroidism if the status of any remaining gland is uncertain after prior parathyroidectomy attempts.